The potentials of farmers’ indigenous knowledge for the control of plant diseases. (2000)
For the whole world to achieve the most desired sclf-sufficiency in food production, plant protection technologies must continuously be developed and used in food production process to battle against prevailing insect pests and diseases, weeds, vertebrate pests and menace of birds. These technologies must reach the primary producers who must be able to use them effectively and efficiently. However, a host of technologies have been developed which arc actually not being used by resource poor farmers who still produce the bulk of food in the developing countries. In Nigeria for example, Olayidc et al (1980) reported that 98% of the food consumed is produced by small-scale farmers who cannot afford Capital and input intensive crop protection approach. Strategies must therefore be developed to make sure that plant protection technologies be developed from farmers indigenous knowledge and selected modern technologies.